Surveillance of some bacterial causative agents of nosocomial infections during the war and peace period - Šuljagić Vesna; Mirović Veljko; Tomanović Branka (Vojnosanitetski Pregled)
Surveillance based on laboratory findings of bacteria isolated from hospitalized patients is an important activity in epidemiologic surveillance of nosocomial infections. It provides the insight into the circulation and management of some causative agents of nosocomial infections in hospitals which facilitates defining of proper measures for the prevention and suppression of nosocomial infections caused by these agents. The aim of this study was to analyze and compare surveillance data collected in Military Medical Academy (MMA) during June 1999 (the period of war) and June 2000 (the period of peace). Isolation frequency of bacteria that were the most common agents of nosocomial: Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli, Acinetobacter spp. and Enterococcus spp., was monitored in patients from 5 various surgical wards of MMA. In the war period, the increase of number of isolates of all these bacteria was registered, but the increase of isolated Acinetobacter spp. was the most significant. The total number of isolates was greater in June 1999 in comparison to June 2000. Most isolates were recovered from wound cultures when the increased number of Enterococcus spp. Methicillin-resistant Staphylococcus aureus isolated from the blood was registered. In the period of peace isolates of Pseudomonas aeruginosa manifested reduced resistance to quinolones, imipenem and 3rd generation cephalosporins. Barrier infection control measures are necessary in preventing nosocomial transmission particularly in the wartime. Thus, preventive medicine is important for performing efficient surveillance, and suggesting the adequate measures for prevention and repression of nosocomial infections, particularly in the period of war.